Meningkatkan Motivasi Belajar Siswa Melalui Model Pembelajaran Kooperatif Tipe Jigsaw Pada Pembelajaran PPKn di Kelas X-1 SMA Negeri 13 Medan - Susanti, Elfa; Kesuma, Sapta; Muslim, Yusnita (Innovative: Journal Of Social Science Research, 2024)
The aim of this classroom action research is to increase student learning motivation in class X-1 at SMA Negeri 13 Medan by implementing the Jigsaw type Cooperative Learning Model in the learning process for Civics subjects. This research was carried out in two learning cycles. The subjects of this research were class X-1 students at SMA Negeri 13 Medan for the 2024/2025 academic year with a total of 36 students. Data collection uses a questionnaire. The analysis findings show that the average level of student learning motivation in cycle I was 75.85% (medium category) and increased in cycle II to 82.73% (high category). The results of the analysis show that implementing the Jigsaw type cooperative learning model can foster student learning motivation in Civics subjects.